Supertetrahedral polyanionic network in the first lithium phosphidoindate Li3InP2 – structural similarity to Li2SiP2 and Li2GeP2 and dissimilarity to Li3AlP2 and Li3GaP2. Issue 4 (8th December 2020) - Restle, Tassilo M. F.; Deringer, Volker L.; Meyer, Jan; Raudaschl-Sieber, Gabriele; Fässler, Thomas F.
Abstract : Li3 InP2 exhibits a polyanionic framework of corner-sharing InP4 tetrahedra and DFT computations reveal the stability trend for indium in the tetragonal structure compared to the orthorhombic structure of the lighter homologues. Abstract : Phosphide-based materials have been investigated as promising candidates for solid electrolytes, among which the recently reported Li9 AlP4 displays an ionic conductivity of 3 mS cm −1 . While the phases Li–Al–P and Li–Ga–P have already been investigated, no ternary indium-based phosphide has been reported up to now. Here, we describe the synthesis and characterization of the first lithium phosphidoindate Li3 InP2, which is easily accessible via ball milling of the elements and subsequent annealing. Li3 InP2 crystallizes in the tetragonal space group I 41 / acd with lattice parameters of a = 12.0007(2) and c = 23.917(5) Å, featuring a supertetrahedral polyanionic framework of interconnected InP4 tetrahedra. All lithium atoms occupy tetrahedral voids with no partial occupation. Remarkably, Li3 InP2 is not isotypic to the previously reported homologues Li3 AlP2 and Li3 GaP2, which both crystallize in the space group Cmce and feature 2D layers of connected tetrahedra but no supertetrahedral framework. DFT computations support the observed stability of Li3 InP2 . A detailed geometrical analysis leads to a more general insight into the structural factors governing lithium ion mobility in phosphide-based materials: in the non-ionic conducting Li3 InP2 the Li ions exclusively occupy tetrahedral voids in the distorted close packing of P atoms, whereas partially filled octahedral voids are present in the moderate ionic conductors Li2 SiP2 and Li2 GeP2 .